Gender- and personality-specific differences in academic qualifications, research motivation, and attractiveness of leadership positions: a survey among radiologists from Germany - Molwitz, Isabel; Kemper, Christoph; Stahlmann, Katharina; Yamamura, Jin; Adam, Gerhard; Langenbach, Marcel Christian; Reim, Martin; Wegner, Franz; Bannas, Peter; Lotz, Joachim; Can, Elif; Zagrosek-Regitz, Vera; Hamm, Bernd; Keller-Yamamura, Sarah (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
This study investigated gender- and personality-specific differences in academic qualifications, research motivation, and options to increase the attractiveness of leadership positions in radiology.A validated questionnaire with 66 questions was distributed via the German Roentgen Society and individually sent to 4,500 radiologists in Germany. Participants were asked about their gender. Personality dimensions were assessed using the OCEAN (Big Five) model. Multivariable regression analyses were employed.Of 510 included participants (women 237 (46.5%)), men were four times more likely to have acquired an associated professorship (AP, Habilitation Privatdozent) ((odds ratio (OR) 4.39 (2.22–8.67)). Also, they planned to achieve an AP more frequently (OR 2.87 (1.47–5.61)). The only gender-specific motivator for an AP was the option to become eligible for the position of chief physician (men OR 2.56 (1.07–6.15)). Mentors increased the probability of acquiring an AP (OR 2.07 (1.13–3.80)) or striving for an AP (4.82 (2.39–9.73)). Female mentees were likelier to have female mentors (OR 4.62 (1.68–12.73)). To increase the attractiveness of leadership positions, female radiologists perceived gender balance at the management level (OR 3.32 (2.28–4.82)), top sharing (OR 2.22 (1.48–3.32)), and better work-life balance (OR 2.02 (1.19–3.43)) as more relevant than male radiologists. More pronounced openness (OR 1.62 (1.10–2.38)) and extroversion (OR 1.45 (1.07–1.97)) were positively associated with planning an AP. More pronounced agreeableness (OR 0.67 (0.50–0.91)) was negatively associated.Research motivation is mainly independent of gender. Academic qualification varies with gender and personality dimensions. Mentoring, female role models, top sharing, and better work-family compatibility could motivate women to pursue academic leadership.Diese Umfrage untersucht gender- und persönlichkeitsspezifische Unterschiede in der akademischen Qualifikation, Forschungsmotivation und von Faktoren zur Steigerung der Attraktivität von Leitungspositionen in der Radiologie.Der Fragebogenversand erfolgte u.a. über Verteiler der Deutschen Röntgengesellschaft sowie durch individualisierte Mailanfragen an 4500 Radiolog:innen in Deutschland. Die subjektive Geschlechtswahrnehmung (Gender) wurde erfragt. Persönlichkeitsdimensionen wurden anhand des OCEAN-Modells (Big Five) erhoben. Analysen erfolgten mittels multivariabler Regressionen.Von 510 Teilnehmenden (Frauen 237 (46,5%)) waren Männer viermal so oft habilitiert (Odds ratio (OR) 4,39 (2,22–8,67)) und planten dies häufiger (OR 2,87 (1,47–5,61)). Der einzige genderspezifische Unterschied in der Motivation zur Habilitation bestand darin, dass Männer eher als Frauen durch das Berufsziel einer Chefarztstelle motiviert waren (OR 2,56 (1,07–6,15)). Mentor:innen erhöhten die Wahrscheinlichkeit habilitiert zu sein (OR 2,07 (1,13–3,80)) oder dies zu planen (4,82 (2,39–9,73)). Weibliche Mentees hatten häufiger weibliche Mentoren (OR 4,62 (1,68–12,73)). Zur Steigerung der Attraktivität von Leitungspositionen war für Radiologinnen häufiger als für Radiologen eine Geschlechterbalance auf Leitungsebene (OR 3,32 (2,28–4,82)), die Teilung von Führungsaufgaben (OR 2,22 (1,48–3,32)) und eine bessere Vereinbarkeit von Beruf und Familie (OR 2,02 (1,19–3,43)) entscheidend. Eine stärkere Ausprägung der Persönlichkeitsdimensionen Offenheit (OR 1,62 (1,10–2,38)) und Extrovertiertheit (OR 1,45 (1,07–1,97)) war positiv assoziiert mit der Planung einer Habilitation, stärker ausgeprägte Verträglichkeit (OR 0,67 (0,50–0,91)) negativ.Forschungsmotivation ist weitgehend genderunabhängig. Die akademische Qualifikation variiert mit Gender und Persönlichkeitsdimensionen. Die Attraktivität von Leitungspositionen kann für Radiologinnen durch Mentorinnen, Vorbilder, Top-Sharing und bessere Vereinbarkeit von Beruf und Familie gesteigert werden.
Keywords: Radiology; Research Priorities; Career Choice; Gender Equality; Personality Assessment